2015
DOI: 10.15640/ijgws.v3n2a7
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of Blame to Victim and Attitudes toward Partner Violence: Cross-National Comparisons across the United States, South Africa, and Nigeria

Abstract: Although knowledge about attribution of blame and partner violence has increased over the past decades, comparative knowledge across countries is sparse. This cross-sectional survey examined cross-national differences in attribution of blame and attitudes toward partner violence among 363 respondents in the United States, South Africa, and Nigeria. Results suggest that female respondents were less likely than male respondents to attribute blame to the female victim or endorse partner violence. Respondents in N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The findings that adolescents from Nigeria were more likely to be exposed to both IPV and family violence than adolescents from South Africa provide a unique opportunity to understand cross-national differences in experience among adolescents in the two countries, especially given the lack of comparative knowledge about these differences. Although comparative knowledge about adolescents is minimal, the finding that adolescents from Nigeria were more likely to endorse beliefs about VAW than adolescents from South Africa is consistent with previous studies that found adult respondents in Nigeria to be more likely to endorse VAW and gender stereotypes than respondents in South Africa (Fakunmoju & Bammeke, 2017;Fakunmoju et al, 2016). Altogether, these findings can be explained by some macro-level differences between the two countries as discussed below.…”
Section: Effects Of Gender and Country On Exposure To Ipv Exposure To Family Violence And Beliefs About Vawsupporting
confidence: 88%
See 1 more Smart Citation
“…The findings that adolescents from Nigeria were more likely to be exposed to both IPV and family violence than adolescents from South Africa provide a unique opportunity to understand cross-national differences in experience among adolescents in the two countries, especially given the lack of comparative knowledge about these differences. Although comparative knowledge about adolescents is minimal, the finding that adolescents from Nigeria were more likely to endorse beliefs about VAW than adolescents from South Africa is consistent with previous studies that found adult respondents in Nigeria to be more likely to endorse VAW and gender stereotypes than respondents in South Africa (Fakunmoju & Bammeke, 2017;Fakunmoju et al, 2016). Altogether, these findings can be explained by some macro-level differences between the two countries as discussed below.…”
Section: Effects Of Gender and Country On Exposure To Ipv Exposure To Family Violence And Beliefs About Vawsupporting
confidence: 88%
“…Religion plays a stronger role in Nigeria (Igbelina-Igbokwe, 2013), which prides itself on religious observance and where it is argued that women's subordination is divinely ordained. Extensive research in various contexts, including South Africa, have indicated that many religious practices reinforce traditional gender roles and in some cases even chastisement of women for transgressing these norms (Fakunmoju et al, 2016;Frahm-Arp, 2015;Johnson, 2015). As argued by Igbelina-Igbokwe (2013) with respect to Nigeria, religion remains a weapon of subjugation of women, of gaining compliance with expected behaviors from women, of maintaining male privileges, and of minimizing resistance to oppressive norms.…”
Section: Effects Of Gender and Country On Exposure To Ipv Exposure Tmentioning
confidence: 99%
“…Nevertheless, research indicates that computerized or online data are suitable for explanatory research (Briones & Benham, 2017;Walter et al, 2018). Several studies have utilized the online mode of data collection (Fakunmoju et al, 2015(Fakunmoju et al, , 2016a(Fakunmoju et al, , b, 2017Buchanan & Smith, 1999;Olatunji et al, 2015;Stanton, 1998) and results indicate that data that are collected in paper-and pencil format are equivalent to those that are collected online (Colasante et al, 2019;Gosling et al, 2004;Lewis et al, 2009;Weigold et al, 2013) across countries (De Beuckelaer & Filip Lievens, 2009). Moreover, respondents in this study appeared to be educated young adults, suggesting that the findings may not be generalizable to less educated older adults.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…In this context, not only have governments at the central and local level failed to prioritise the protection of women from sexual harassment; there is also victim-blaming, stigmatisations and endemic rejection within society. 62 The situation has influenced them to seek protectionif necessary, by selling their bodies to security agents in exchange for that protection. One NGO worker stated 'there are reports where you have the military, civilian joint task force and police … involved and using sex as a tool to provide protection for the victims'.…”
Section: Trade By Barter: Sex For Food Money and Protectionmentioning
confidence: 99%